The Crystal Structure of 3-Amino-1-(4-Chlorophenyl)-9-Methoxy-1H-Benzo[f]Chromene-2-Carbonitrile: Antimicrobial Activity and Docking Studies - Rawda M. Okasha; Ahmed M. Fouda; Majed A. Bajaber; Hazem A. Ghabbour; Abd El-Galil E. Amr; Ahmed M. Naglah; Abdulrahman A. Almehizia; Ahmed A. Elhenawy; Ahmed M. El-Agrody (Crystals, 2022)
Compound 3-amino-1-(4-chlorophenyl)-9-methoxy-1H-benzo[f]chromene-2-carbonitrile (4), was synthesized via the reaction of 7-methoxynaphthalen-2-ol (1), 4-chlorobenzaldehyde (2), and malononitrile (3) in an ethanolic piperidine solution under microwave irradiation. The synthesized pyran derivative 4 was asserted through spectral data and X-ray diffraction. The molecular structure of compound 4 was established unambiguously through the single crystal X-ray measurements and crystallized in the Triclinic, P-1, a = 8.7171 (4) Å, b = 10.9509 (5) Å, c = 19.5853 (9) Å, α = 78.249 (2)°, β = 89.000 (2)°, γ = 70.054 (2)°, V = 1717.88 (14) Å3, Z = 4. The target molecule has been screened for antibacterial and antifungal functionality. Compound 4 exhibited favorable antimicrobial activities that resembled the reference antimicrobial agents with an IZ range of 16–26 mm. In addition, MIC, MBC, and MFC were assessed and screened for molecule 4, revealing bactericidal and fungicidal effects. Lastly, a molecular docking analysis was addressed and conducted for this desired molecule.